MORPHOLOGICAL FEATURES OF THE ANTERIOR PITUITARYS OF CHILDREN WHO DIED BEFORE THE AGE OF 6 MONTHS FROM HIV-INFECTED MOTHERS - Sherstiuk, S.A.; Sorokina, I.V.; Ремнева, Н.О. (World of Medicine and Biology, 2012)
In the anterior pituitary of children dying before the age of 6 months from HIV-infected mothers showed high abilities of adaptive-compensatory mechanisms, apparently due to the influence of chronic hypoxia and manifested by a decrease in the diameter of the cells, the size of their secretory granules and increased nuclear-cytoplasmic ratio in entire population chromofilic cells as well as an increase in the relative volume chromofilicendocrine cells due to chromophobic.